VapC12 ribonuclease toxin modulates host immune response during Mycobacterium tuberculosis infection - Tyagi, Shaifali; Sadhu, Srikanth; Sharma, Taruna; Paul, Abhijit; Pandey, Manitosh; Nain, Vaibhav Kumar; Rathore, Deepak Kumar; Chatterjee, Samrat; Awasthi, Amit; Pandey, Amit Kumar (Frontiers in Immunology, 2024)
Mechanistic understanding of antibiotic persistence is a prerequisite in controlling the emergence of MDR cases in Tuberculosis (TB). We have reported that the cholesterol-induced activation of VapC12 ribonuclease is critical for disease persistence in TB. In this study, we observed that relative to the wild type, mice infected with ΔvapC12 induced a pro-inflammatory response, had a higher pathogen load, and responded better to the anti-TB treatment. In a high-dose infection model, all the mice infected with ΔvapC12 succumbed early to the disease. Finally, we reported that the above phenotype of ΔvapC12 was dependent on the presence of the TLR4 receptor.Overall, the data suggest that the inability of ΔvapC12 to resolve neutrophil-mediated inflammation reduced bacterial killing by altering the T-cell response. Overall, the data suggests that failure of a timely resolution of the early inflammation by the ΔvapC12 infected mice led to hyperinflammation, altered T-cell response and high bacterial load. In conclusion, our findings suggest the role of the VapC12 toxin in modulating the innate immune response of the host in ways that favor the long-term survival of the pathogen inside the host.